2011
DOI: 10.2147/ndt.s14385
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the risperidone formulations in the management of schizophrenia

Abstract: Risperidone is one of the early second-generation antipsychotics that came into the limelight in the early 1990s. Both the oral and long-acting injectable formulations have been subject to numerous studies to assess their safety, efficacy, and tolerability. Risperidone is currently one of the most widely prescribed antipsychotic medications, used for both acute and long-term maintenance in schizophrenia. Risperidone has better efficacy in the treatment of psychotic symptoms than placebo and possibly many first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…It has been suggested that hyperprolactinaemia in patients treated with risperidone-LAI or PP is driven by 9-hydroxyrisperidone and the higher occupancy of D2 at the pituitary level compared with the striatum (Madaan et al, 2011). It has been suggested that hyperprolactinaemia in patients treated with risperidone-LAI or PP is driven by 9-hydroxyrisperidone and the higher occupancy of D2 at the pituitary level compared with the striatum (Madaan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that hyperprolactinaemia in patients treated with risperidone-LAI or PP is driven by 9-hydroxyrisperidone and the higher occupancy of D2 at the pituitary level compared with the striatum (Madaan et al, 2011). It has been suggested that hyperprolactinaemia in patients treated with risperidone-LAI or PP is driven by 9-hydroxyrisperidone and the higher occupancy of D2 at the pituitary level compared with the striatum (Madaan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The range is in line with the current Japanese label of risperidone recommending 2‐6 mg/d and the US FDA current label not recommending doses above 6 mg/d, although both labels also allow a higher dose of risperidone. Several clinical studies indicated that risperidone at a dose higher than 6 mg/d might induce side effects such as extrapyramidal symptoms . The dose was increased by 4 mg/d for blonanserin and 1 mg/d for risperidone if the change from baseline in the Brief Psychiatric Rating Scale (BPRS, see Section 2.4) total score at the study visit was −5 or higher and no major safety concern was observed.…”
Section: Methodsmentioning
confidence: 99%
“…Several clinical studies indicated that risperidone at a dose higher than 6 mg/d might induce side effects such as extrapyramidal symptoms. 8,9 The dose was increased by 4 mg/d for blonanserin and 1 mg/d for risperidone if the change from baseline in the Brief Psychiatric Rating Scale (BPRS, see Section 2.4) total score at the study visit was −5 or higher and no major safety concern was observed. If a major safety concern was found, a dose reduction was allowed.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Overall, we demonstrate a sex-dependent regulation of peripheral inflammatory hyperalgesia by the PRL system. prolactin receptor; transient receptor potential V1; transient receptor potential A1; transient receptor potential M8; female; inflammation; pain MANY HUMAN CHRONIC INFLAMMATORY conditions are associated with hyperprolactinemia, and this increase in prolactin (PRL) levels can lead to serious health issues related to cancer, infertility, inflammatory diseases, and body weight (11,42,48,73). Human inflammatory conditions with increased PRL serum levels include the severe form of progressive systemic sclerosis (34, 69), the active phase of systemic lupus erythematosus (37, 74), rheumatoid arthritis (44), polymyalgia rheumatica (68), and autoimmune thyroid diseases (26).…”
mentioning
confidence: 99%